Location of distribution centers through multicriteria analysis - Pinto, Ana Giulia Nascimento; Freitas, Cláudia Regina de; Luche, José Roberto Dale (Brazilian Journal of Production Engineering, 2024)
The location of a distribution center (DC) can add significant value to a company by ensuring deliveries arrive on schedule and/or expanding its customer base. The criteria analyzed in decision-making for determining an industrial unit are often subjective, with each expert bringing different knowledge based on their professional experience. Therefore, transforming this data to enable a multicriteria analysis is essential. This case study evaluates the establishment of distribution centers in the state of São Paulo, considering cities with client locations. Using data from eleven clients and considering city centers as reference points, the clients were divided into three groups. Three possible locations were analyzed for Group 1, four for Group 2, and two for Group 3. Fuzzy Theory was applied, involving the stages of Fuzzification, Rule Base, Inference, and Defuzzification, converting subjective criteria into numerical values to determine the best location for each group. The results indicated Sorocaba as the ideal location for Group 1, Bragança Paulista for Group 2, and São José dos Campos or Caçapava for Group 3, both meeting the criteria after defuzzification.
Keywords: Fuzzy Logic; Distribution Center; Multicriteria Analysis